(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Uzbekistan’s energy sector is overwhelmingly fossil‑fuel based. In 2019, natural gas accounted for over 90% of primary energy production. Electricity generation has similarly relied on thermal power (gas/coal) and hydropower; renewables beyond hydro were negligible until recently. Total domestic energy supply in 2019 was about 47.1 Mto, with oil and coal contributing the remainder and hydropower about 1%. In practice, renewables (solar, wind, hydro, bio) provided roughly 10% of electricity in 2019 and early 2020.